Prayana: A Journey Towards Financial Inclusion - Mehra, Apurv; Satija, Sambhav; O'Neill, Jacki (ICTD'17, 2017)
In this paper we present a solution built to improve loan management for auto-rickshaw drivers in Bangalore. As part of a bid to increase financial inclusion, a social enterprise (TWU) supports drivers in taking loans from mainstream banks to purchase their auto-rickshaws. Findings from an ethnographic study show that whilst providing a vital service, TWU managed its processes through an ad hoc mixture of paper and technology. Their processes enable the flexibility crucial for supporting a financially-vulnerable community, but unfortunately important information was often not to-hand, leading to sub-optimal decisions being made about loan allocation. We developed and deployed an integrated technical solution to support TWU’s work. In this paper, we describe the back-office solution and how it has assisted the organization in streamlining its operations, supporting more informed decision making and providing the opportunity to scale-up their operations.